SOME CONSUMER PROTECTION ISSUES IN ELECTRONIC COMMERCE (Journal of actual problems of jurisprudence, 2025)
With modern development, digitalization in many countries is becoming a strategic priority area of economic development. The digital economy is an economic activity carried out through the internet, mobile communications, digital technologies, that is, virtual reality, in economic relations on production, distribution, exchange and consumption.The author gives a number of author's recommendations in the article for the systematic formation of the structure of an online store, e-commerce to increase the competitiveness of e-commerce, indicating that in addition to effective opportunities in the development of e-commerce, there are risks that threaten. Among them are the creation of a national research organization to improve the conditions for the development of digital business, the provision of land by the state for the construction of warehouses in the regions in the development of digital commerce, as well as the improvement of logistics networks, the use of new innovative models in the technological modernization of certain sectors of the economy, the introduction of new types of business plans, the approval of modern structures of public service.Given the dynamic development of digital business, in addition to traditional trade, IT specialists are in high demand in accordance with the requirements of the time.  At the same time, the author emphasizes the need to take state measures to train specialists in the field of digital commerce, including the organization of special courses or programs for rural residents in the regions.In order to strengthen the protection of consumer rights, the new version of the law «Оn protection of Consumer Rights» provides for additional regulatory measures. As we all know, such refined concepts as «electronic sales platform (marketplace)», «online store» and «information and advertising platform» have been introduced into the law. At the same time, the author proposes to introduce the term «e-commerce» and give it a scientifically consistent definition. According to the author, e-commerce contributes to the settlement of issues of consumer violations that occur when ordering services and works with a mobile phone.The article also proposes to ensure the mandatory protection of personal data about consumers and supplement the inadmissibility of claims by entrepreneurs that violate and (or) oppress the rights and legitimate interests of consumers.Keywords: digital economy, e-commerce, consumer, consumer rights, seller, buyer, digital environment, online store.